Uma estratégia de investimento baseada no padrão de divergência no indicador de análise técnica MACD - Martins, Marcus Vinicius Araujo (2015)
This dissertation includes the implementation of an investment strategy using the divergence pattern of Technical Analysis indicator MACD. This pattern, when it occurs in historical price series indicate trend reversals and thus signal moments of buying and selling of shares, within the so-called Capital Markets. An investment strategy composed of a pattern detection algorithm divergence of the MACD indicator was implemented and applied to several historical series of american stock prices considering trade volumes, popularity of the company, price volatility and their comparison with returns on random dates market entrance. In addition, a stock portfolio composed of the higher volume trading and more volatile stocks was implemented. These tests considered the period from 2003 to 2013. Another test on definite trend moments and not definite considered the interval from 2000 to 2013. Overall, all the tests and simulations, were obtained positive returns on investments based on past prices using a strategy when compared with simple strategies such as buy a stock and hold it till the end of the period, or in comparison with major indexes in the US market. One can conclude, therefore, that the divergence pattern of the MACD indicator was able to predict reversals trends in stock prices used as reference during the period.